Echocardiographic Study on Ischemic Heart Disease Masquerading as Dilated Cardiomyopathy - FUJIWARA, TADASHI (Juntendo Medical Journal, 1985)
The purpose of this study was to determine whether two-dimensional echocardiography (TDE) can differentiate ischemic heart disease (IHD) from dilated cardiomyopathy (DCM) The subjects consisted of six patients with IHD (Group I) who showed left ventricular dilatation and diffuse abnormality of wall motion, but did not manifest obvious localized myocardial infarction or left ventricular aneurysm on TDE, and 26 patients with DCM, postmyocarditic cardiomegaly and alcoholic heart disease (Group II). A short-axis image of the left ventricle obtained by TDE at the chordal and the papillary muscle levels was divided into four quadrants. Regional wall motion abnormality (asynergy) with reference to systolic thickening was analyzed qualitatively in each segment. It was studied whether the anterior or posterior two segments showed discordance in grade of asynergy (discordance) at each level. A pathological study was also performed on five autopsied hearts in order to compare the grade of asynergy with the severity of myocardial degeneration and fibrosis in the same segment.The results were as follows :1) M-mode echocardiography : The mean LVDd showed no significant difference between the two groups. Eight patients in group II showed marked left ventricular dilatation (LVDd≥ 75 mm), but there were no such cases in group I.2) Regional wall motion : Five group I patients showed discordance in the posterior two segments, while in group II, only one case out of all those with mild left ventricular dilatation, who had received a ventricular pacemaker implant, showed discordance in the anterior and posterior two segments. Six of the patients with marked left ventricular dilatation showed discordance in the anterior or posterior two segments. No group I patient showed discordance in both sides.3) The pathological study : In one patient in group I, the severity of myocardial degeneration and fibrosis was well correlated with the grade of asynergy, but in three group II cases except one case there was no correlation between these two findings.